If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/5 (3x+4)=4 (2-2x)+14
We simplify the equation to the form, which is simple to understand
3/5(3x+4)=4(2-2x)+14
Simplifying:
+ 0.6*(3x+4)=4*(2-2x)+14
Reorder the terms in parentheses
+(+1.8x+2.4)=4*(2-2x)+14
Remove unnecessary parentheses
+1.8x+2.4=+4+*(+2-2x+)+14
Reorder the terms in parentheses
+1.8x+2.4=+(+8-8x)+14
Remove unnecessary parentheses
+1.8x+2.4=+8-8x+14
We move all terms containing x to the left and all other terms to the right.
+1.8x+8x=+8+14-2.4
We simplify left and right side of the equation.
+9.8x=+19.6
We divide both sides of the equation by 9.8 to get x.
x=2
| y=0.7(30)+123 | | g+4.6=19.3 | | F(-1)=-3+1 | | y*y+3y=0 | | x/-4+(-50)=-76 | | y=-0.7(20)+123 | | 25x^2-9=7 | | 6x-4=8-6x | | 2.5p=q+-1.6 | | -(x-4)=-22 | | y=5+4 | | 12c^2+8c+1=o | | y=4+4 | | y=3+4 | | -8+4y=4-6-3y-2 | | 1/5(5+5k)=4 | | 1x-y=1 | | 3j-8-5j=16 | | (0)=2y-3 | | 5n+3=2(1.4x+3) | | 4(t-8)+2t=14 | | 5/3-2b/-7=8 | | (3x+y)/c=4 | | 2/3(2x-1)+21/3=7+1/2x | | 3(6s+2)-6s=3(4s+3)-13 | | (x+2)(x-5)(x+11)=0 | | -3(1+3x)=-75 | | 5(-5x-8)=-340 | | -9.5=u/2.72 | | y=-5+4 | | x^3+5x^2+2x+10=0 | | -69(y-16)=y-(-88) |